Delignification of Wood Chips and Pulps by Using Natural and Synthetic Porphyrins: Models of Fungal Decay - Paszczyński, Andrzej (1988)
Kraft pulps, prepared from softwoods, and small chips of birch wood were treated with heme and tert-butyl hydroperoxide in aqueous solutions at reflux temperature. Analyses of treated pulps showed decreases in kappa number (a measure of lignin content) from about 36 to less than 2, with concomitant increases in brightness (80% increase in the better samples). Analyses of treated wood chips revealed selective delignification and removal of hemicelluloses. After 48 h of treatment, lignin losses from the wood chips approached 40%, and xylose/mannose (hemicellulose) losses approached 70%, while glucose (cellulose) losses were less than 10%. Examination of delignified chips by transmission electron microscopy showed that the removal of lignin occurred in a manner virtually indistinguishable from that seen after decay by white rot fungi. Various metalloporphyrins, which act as biomimetic catalysts, were compared to horseradish peroxidase and fungal manganese peroxidase in their abilities to oxidize syringaldazine in an organic solvent, dioxane. The metalloporphyrins and peroxidases behaved similarly, and it appeared that the activities of the peroxidases resulted from the extraction of heme into the organic phase, rather than from the activities of the enzymes themselves. We concluded that heme-tert-butyl hydroperoxide systems in the absence of a protein carrier mimic the decay of lignified tissues by white rot fungi.